The role of formalised and non-formalised intentions in legal parent-child relationships in Dutch law - Machteld Vonk (Utrecht Law Review, 2008)
This article aims to explore the role that the formalised and non-formalised intentions of legal and prospective parents may play in the attribution of parental status in Dutch law in cases of assisted conception. Such intentions may have been laid down in a contract, have been agreed upon orally or they may not have been expressed and/or agreed upon at all by the parties involved. In the first part of this article the situations in which such intentions may play a role will be inventoried. Subsequently, the (lack of) recognition of these intentions in current parent-child law will be discussed. Finally attention will be paid to the desirability of increased recognition of such intentions in Dutch parent-child law.